2005
DOI: 10.1097/01.jnen.0000186922.42592.b7
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated and Spatial Upregulation of Arc in Striatonigral Neurons Correlates With L-Dopa-Induced Behavioral Sensitization in Dyskinetic Rats

Abstract: Although oral administration of L-Dopa remains the best therapy for Parkinson disease, its long-term administration causes the appearance of abnormal involuntary movements such as dyskinesia. Although persistent striatal induction of some genes has already been associated with such pathologic profiles in hemiparkinsonian rats, molecular and cellular mechanisms underlying such long-term adaptations remain to be elucidated. In this study, using a rat model of L-Dopa-induced dyskinesia, we report that activity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 77 publications
9
53
1
1
Order By: Relevance
“…This is in accordance with the hypothesis that dyskinesias should not be regarded simply as a movement disorder, but also as a limbic and cognitive disorder (Guigoni et al, 2005). In rodents, we did observe a spatial correlation between Nur77 expression and L-DOPA-induced dyskinesia accompanied (whole striatum) or not (lateral part of the striatum) with locomotor sensitization in unilaterally lesioned 6-OHDA rats in a previous report (Sgambato-Faure et al, 2005). However, no attempt to correlate individual Nur77 mRNA levels an intensity of LIDs or locomotor sensitization was made.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This is in accordance with the hypothesis that dyskinesias should not be regarded simply as a movement disorder, but also as a limbic and cognitive disorder (Guigoni et al, 2005). In rodents, we did observe a spatial correlation between Nur77 expression and L-DOPA-induced dyskinesia accompanied (whole striatum) or not (lateral part of the striatum) with locomotor sensitization in unilaterally lesioned 6-OHDA rats in a previous report (Sgambato-Faure et al, 2005). However, no attempt to correlate individual Nur77 mRNA levels an intensity of LIDs or locomotor sensitization was made.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, L-Dopa-induced Nur77 expression is observed in SP cells of the caudate-putamen of MPTP monkeys. This observation is consistent with the modulation of Nur77 in DYN-positive cells in the intact side of unilateral 6-OHDA-lesioned rats (St-Hilaire et al, 2003), as well as with some restricted up-regulation of Nur77 following L-Dopa treatment in the ipsilateral striatum observed in another study (Sgambato-Faure et al, 2005). The modulation of Nur77 observed in the intact striatum following L-Dopa treatment in unilaterally 6-OHDA-lesioned rats, which is similar to the present study following systemic MPTP and L-Dopa treatment, possibly results from an effect on intratelencephalic corticostriatal neurons that send massive inputs to both ipsilateral and contralateral striatum (Ballion et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Accordingly, Centonze et al (2006) have elegantly shown that chronic treatment with cocaine prevents synaptic depotentiation at corticostriatal synapses, an effect that could dictate the persistence of addictive behaviors. Because the same loss of corticostriatal depotentiation was shown after chronic L-DOPA treatment (Picconi et al, 2003), a therapy that strongly promotes Arc up-regulation (Sgambato-Faure et al, 2005), we speculate that increased Arc expression herein reported may contribute, at least in part, to the impaired corticostriatal depotentiation after repeated cocaine administration.…”
mentioning
confidence: 89%
“…We found that unilateral STN-HFS in awake intact or hemiparkinsonian rats induced contralateral forelimb dyskinesia and even contralateral rotation, depending on stimulation parameters and intensity, as observed after STN lesioning (Henderson et al, 1999). Rotational effects were observed at intensities exceeding 190 A and were preceded by orofacial, axial, and forelimb dyskinesias resembling L-3,4-dihydroxyphenylalanine (L-DOPA)-induced dyskinesias in hemiparkinsonian rats (Winkler et al, 2002;Sgambato-Faure et al, 2005). Higher-intensity stimulation was required to elicit dyskinesias in SNc-lesioned than in intact rats, but only for frequen- cies Ͻ130 Hz or pulse widths Ͻ60 s. Sensitivity to STN-HFS therefore differed between the parkinsonian and normal states, as predicted after STN lesioning (Guridi and Obeso, 2001) and consistent with previous studies (Salin et al, 2002).…”
Section: Effects Of Stn Stimulation Parameters On Motor Behaviormentioning
confidence: 99%